(untitled) (Archives of Clinical Psychiatry, 2012)
BACKGROUND: Cannabis sativa (cannabis, marijuana) is a drug of abuse with well known psychoactive effects and therapeutic potential. A large number of cannabinoids chemically similar to Δ9-THC, the main active metabolite of marijuana, were synthesized in an attempt to exclude or minimize the psychotropic effects, maintaining the therapeutic potential. OBJECTIVES: The aim of this work was to review of the use of synthetic cannabinoids as emerging drugs of abuse, especially in the form of spice or herbal blends. METHODS: A bibliographic search was performed in PubMed employing the terms "synthetic cannabinoids", "spice", "legal highs", "herbal blends", "psychosis cannabis" and cross references. RESULTS: A number of synthetic cannabinoids can be found in Spice products, confirming that herbal incense emerged as new drugs of abuse. DISCUSSION: It is unclear whether the use of synthetic cannabinoids and Spice is a fad or will be established as common practice in our society. However, the phenomenon of designer drugs, especially synthetic cannabinoids, will remain a challenge to health authorities in the globalized world, requiring additional clinical and forensic research.